Impact of Work Environment and Work Stressing on The Job Satisfaction of Medical Record Officers - Atma Deharja; Nonik Aisyah Rohman; Rossalina Adi Wijayanti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Factors that influence the work satisfaction of medical record officer is the work environment and work stress. Uncomfortable work environment and work stressing with a lot of work demands make the staff will experience severe pressure. Based on the preliminary study on April 1st, 2018, it's found that seven officers who often absent (above 10%), small workspace, awkward movement, inadequate facilities, double jobs, and double shifts that made 10 out of 13 officers experience unenjoyable in their work. The purpose is to analyze the effect in the work environment and work stressing on the work satisfaction of medical record officers in the X Hospital. It is analytical with a cross-sectional approach using ordinal logistic regression and questionnaire as an instrument. The sample used is 13 medical record officers—the work environment and work stressing as independent variables and work satisfaction as dependent variables. The significance value of the work environment and work stress variable is 0.002. It has a significance value <α (P <0.05), proving that the work environment and work stressing have a significant effect on work satisfaction. This study's suggestions need to be the expansion of workspace, additional facilities, and officers to avoid double jobs and double shifts.